2013
DOI: 10.1016/j.nutres.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Purple grape juices prevent pentylenetetrazol-induced oxidative damage in the liver and serum of Wistar rats

Abstract: Oxidative damages in hepatocytes may be caused by epilepsy and/or anticonvulsant drugs. Epilepsy is one of the most common neurological disorders, characterized by recurrent seizures, which may increase the content of reactive oxygen species. Organic and conventional grape juices are rich in polyphenols, compounds with important antioxidant activity. It is hypothesized that organic and conventional purple grape juices may have protective effect against oxidative damage induced by pentylenetetrazole (PTZ) (a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
7
21
2
Order By: Relevance
“…The anthocyanins were the main phenolic class detected in V. labrusca, hybrid, Tempranillo and Alicante Bouschet grape juices, corresponding to 44.35 to 70.33% of the total phenolic content quantified for the samples. These results were consistent with those described by Rodrigues et al [32] and Stalmach et al [33]. It is known that the anthocyanins are responsible for the coloration of the grape, have the ability to scavenge the excess radicals and may play a role in the prevention of diseases [34][35][36].…”
Section: Characterization Of Grape Juicesupporting
confidence: 92%
“…The anthocyanins were the main phenolic class detected in V. labrusca, hybrid, Tempranillo and Alicante Bouschet grape juices, corresponding to 44.35 to 70.33% of the total phenolic content quantified for the samples. These results were consistent with those described by Rodrigues et al [32] and Stalmach et al [33]. It is known that the anthocyanins are responsible for the coloration of the grape, have the ability to scavenge the excess radicals and may play a role in the prevention of diseases [34][35][36].…”
Section: Characterization Of Grape Juicesupporting
confidence: 92%
“…Trolox/g) lower than that found in the present study. While Rodrigues et al (2013) (21), using the method of reactive substances to the thiobarbituric acid (TBA), using adults rats, divided into 3 groups (control, organic grape juice and conventional grape juice) noted that although the organic juice has higher polyphenol content than the conventional grape juice, both were able to reduce the oxidative damage induced by (pentylenetetrazole) PTZ in plasm of the Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Whole grape juice was administered for 6 days before the induction of cisplatin and then continued for two additional days. In the present study, whole grape juices were administered according to the method proposed by Rodrigues et al 15 The doses of grape juice were determined by calculating the average amount of juice that would be equally consumed daily by a 70 kg human male. 21 Hence, whole grape juices were administered to the rats at 10 mL/g of body weight once per day.…”
Section: Animalsmentioning
confidence: 99%
“…[12][13][14] Consumption of grape juice at a concentration of 10 mL/g body weight in Wistar rats with pentylenetetrazol-induced oxidative damage for 17 days resulted in an improvement in liver and serum oxidative damage by increased enzymatic antioxidant defenses. 15 In addition, grape juice concentrate has been found to protect against oxidative DNA damage induced by hydrogen peroxide (H 2 O 2 ) in peripheral blood cells in rats. 16 Clinical studies have reported that concentrated red grape juice supplementation exerts antioxidant, hypolipidemic, and anti-inflammatory effects in both healthy subjects and hemodialysis patients.…”
mentioning
confidence: 99%